Role Integration Increases the Fungibility of Mentally Accounted Funds - Paul, Iman; Parker, Jeffrey R.; Dommer, Sara Loughran (Journal of Marketing Research, 2023)
Bridging the gap between the mental accounting and identities/roles literatures, the present research examines how the extent to which an individual's life roles (e.g., “employee,” “spouse”) are integrated (i.e., have more flexible and permeable psychological boundaries between them) moderates the fungibility of mentally accounted funds. Specifically, individuals with more integrated roles are more able to circumvent the constraints typically imposed by mental budgeting and earmarking; therefore, they are more likely to use funds that are allocated or budgeted for the purposes of one role to service the needs/wants of another role. This holds regardless of whether funds have been (1) allocated to a broader role-specific mental account for future expenditures or (2) earmarked for a specific purchase. The authors find evidence that the effect of role integration arises because those with more integrated roles believe that making purchases for one role using funds allocated or budgeted for the other role is more justifiable.